PENGARUH RASIO AKTIVITAS, LEVERAGE, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN SEKTOR BARANG KONSUMEN PRIMER - Sawitri, Kadek Dewi; Artini, Luh Gede Sri (Buletin Studi Ekonomi, 2022)
A country’s business growth can increases the competition between the business companies in order to attract investors by increasing the company value.  This study aims to determine the effect of activity ratio, leverage ratio, profitability ratio, and firm size on firm value. This research was conducted at consumer non-cyclical sector companies that are listed on the Indonesia Stock Exhange in 2016-2020 period. Quantitative data with secondary sources published by the Indonesia Stock Exchange was used. The sample used in this study were 25 companies through purposive sampling method. This study used non-participant observation method. The analysis technique used is multiple linear regression. Based on the results of the analysis found that the activity ratio had a negative effect on firm value, the leverage and profitability ratios had a positive effect on firm value, and firm size had no effect on firm value. Investors and company management are expected to pay attention to activity ratio, leverage ratio, and profitability ratio that have an impact on firm value. Keywords: firm value; activity ratio; leverage ratio; profitability ratio; firm size